A Decade of Confusion: The Differing Directions of Social Security and Accident Compensation 1969 – 1979 - McClure, Margaret (Victoria University of Wellington Law Review, 2003)
Overlapping with the implementation of ACC in New Zealand was a parallel review of Social Security, charged with making recommendations for the overall system of social entitlements. The review took place in the context of global economic pressure and changes in family structure during the early 1970s, and represents a marked contrast in tone and ambition from the Woodhouse Commission. This paper contrasts the more modest direction taken by the 1972 Royal Commission on Social Security with the Woodhouse proposals, focusing on such matters as the structure of benefits and the underlying social and community objectives.